Effect of different drying methods on the structure and digestibility of short chain amylose crystals. (January 2016) - Zeng, Feng; Zhu, Siming; Chen, Fuquan; Gao, Qunyu; Yu, Shujuan
Abstract: Short chain amylose (SCA) was obtained by debranched waxy rice starch. The SCA crystals was formed by crystallization and dried by freeze drying, air drying and spray drying. The physicochemical properties and digestibility of the dried crystals were investigated. Light microscope and scanning electron microscopy revealed that the air dried crystals exhibited compact structure, but freeze dried crystals showed loose and porous morphology. Spray dried crystals showed sphere morphology. Air dried crystals had a higher relative crystallinity and a higher melting temperature as compared with the crystals dried by freeze and spray drying. The digestibility analysis showed that air drying was the preferred method for the formation of resistant starch in SCA crystals, while spray drying favor to obtain products with high level of slowly digestible starch. The tight pack of double helix could be responsible for the enzyme resistance of air dried crystals. Graphical abstract: Highlights: Short chain amylose (SCA) was obtained by debranched waxy rice starch. SCA was recrystallized to form SCA crystal. The SCA crystals were dried by freeze drying, air drying and spray drying. The spray dried crystals showed sphere morphology. Structural difference in SCA crystals affected their digestibility.